Hemocompatibility of hyaluronan enhanced linear low-density polyethylene for heart valve leaflet applications - Simon-Walker, Rachael, author; Popat, Ketul C., advisor; Reynolds, Melissa, committee member; Orton, Christopher, committee member; Chicco, Adam, committee member (Colorado State University. Libraries, 2018)
Heart valve disease is a major concern in both developed countries with advanced ageing populations and undeveloped countries which experience a high incidence of rheumatism leading to valvular disease. To reduce mortality and improve quality of life, heart valve implantations have been widely used to assist in improving function of the native cardiovascular system. While mechanical heart valves and tissue-based heart valves have been successfully used to improve quality of life compared to untreated valvular disease, draw-backs are inherent. Mechanical heart valves are prone to thrombosis and require life-long supplemental anti-coagulation therapy. Tissue-based valves are more hemocompatible, but lack the durability required for long-term implantation. To address these issues, polymeric heart valves have been highly sought after due to polymers' abilities to enhance durability and be manufactured to be similar to the native heart valve leaflet. In addition, their surfaces can be modified to increase hemocompatibility. In this work we explore the hemocompatibility and immune response to a novel polymer for use in heart valve leaflet applications; hyaluronan enhanced linear low-density polyethylene. It is proposed that the combination of linear low-density polyethylene with hyaluronan will create a highly durable material that will reduce thrombosis and inflammation due to the anionic and hydrophilic nature of the glycosaminoglycan.
Keywords: heart valves; immune response; polymers; hemocompatibility; biomaterials; platelets